Cd44 deletion suppresses atypia in the precancerous mouse testis. Issue 5 (28th January 2019) - Li, Huaibiao; Shukla, Shalmali; Frappart, Lucien; Herrlich, Peter; Ploubidou, Aspasia
Abstract : Loss‐of‐function of RHAMM causes hypofertility and testicular atrophy in young mice, followed by germ cell neoplasia in situ (GCNIS) of the testis, cellular atypia, and development of the testicular germ cell tumor (TGCT) seminoma. These pathologies reflect the risk factors and phenotypes that precede seminoma development in humans and—given the high prevalence of RHAMM downregulation in human seminoma—link RHAMM dysfunction with the aetiology of male hypofertility and GCNIS‐related TGCTs. The initiating event underlying these pathologies, in RHAMM mutant testis, is premature displacement of undifferentiated progenitors from the basal compartment. We hypothesized that cd44 (both cancer initiating cell‐ and oncogenic progression marker) will drive GCNIS development, induced by RHAMM‐loss‐of‐function in the mouse. We report that cd44 is expressed in a specific subset of GCNIS testes. Its genetic deletion has no effect on GCNIS onset, but it ameliorates oncogenic progression. We conclude that cd44 expression, combined with RHAMM dysfunction, promotes oncogenic progression in the testis.